Absorption of N, P and K Nutrients of Sweet Corn Plants (Zea Mays Saccharata Sturt) Due to the Application of Urea, Sp-36, Kcl Fertilizers and Biofertilizer on Fluventic Eutrudepts from Jatinangor - Sofyan, Emma Trinurani; Machfud, Yuliati; Yeni, Hilma; Herdiansyah, Ganjar (Jurnal Agrotek Indonesia, 2019)
Availability of nutrients in the soil greatly affect the condition of plants' growth and development. Fertilization is one of the exact ways to increase nutrients in the soil. Usage of inorganic fertilizer intensively and routinely can decrease soil fertility level and create residual that will damage to the environment. This research aims to determine the effect of fertilizer dose combination of N, P, K, and Biofertilizer to uptake N, P and K on sweet corns (Zea mays Saccharata Sturt) in Fluventic Eutrudepts from Jatinangor. Dose combination was expected can reduce fertilizer dose N, P, K without decreasing productivity and crop yields. This research was performed from January until April 2018 at Experimental Field Faculty of Agriculture, Padjajaran University, Jatinangor, Sumedang, West Java at 725 m asl. Experimental design used in this research is Randomized Block Design (RBD) with 10 treatments and 3 replications which consist of treatments 0 N, P, K + 0 biofertilizer; 1 N, P, K + 0 biofertilizer; 0 N, P, K + 1 biofertilizer; 1/4 N, P, K + 1 biofertilizer; 1/2 N, P, K + 1 biofertilizer; 3/4N, P, K + 1 biofertilizer; 1 N, P, K + 1 biofertilizer; 3/4 N, P, K + 1/4 biofertilizer; 3/4 N, P, K + 1/2 PHC; 3/4 N, P, K + 3/4 biofertilizer. Recommended dosage was 300 kg of urea, 150 kg of SP 36, and 50 kg KCl ha-1 and 5 L ha-1 biofertilizer. The results showed a significant effect of the combination N, P, K fertilizer and biofertilizer to uptake N, P, K, and best dose combination was showed by treatment 1/2 N P K + 1 biofertilizer